2012
DOI: 10.1063/1.4740273
|View full text |Cite
|
Sign up to set email alerts
|

Application of well-defined indium tin oxide nanorods as Raman active platforms

Abstract: We determine the surface enhanced Raman (SER) capability of indium tin oxide nanorods (ITO NRs) whose physical, chemical, and optical properties are precisely and uniformly controlled during synthesis. We demonstrate that the Raman intensities observed from varying concentrations of the pure and mixed molecules of rhodamine 6G and 4 0 ,6-diamidino-2-phenylindole are much larger on ITO NRs relative to those measured on commercially available ITO-coated glass or Si. Our efforts signify the first attempt to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In this regard, we have previously demonstrated the different uses of indium tin oxide nanowire (ITO NW) network systems in biomolecular fluorescence and surface-enhanced Raman signal detection. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we have previously demonstrated the different uses of indium tin oxide nanowire (ITO NW) network systems in biomolecular fluorescence and surface-enhanced Raman signal detection. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [39] synthesized ITO nanorods by thermal evaporation using gold as seed layer and tested these surfaces as SERS substrates. They obtained very good results and assigned them to the SERS effect from the ITO nanorods.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the research on ITO nanomaterials has attracted much attention due to the potential of developing applications in the miniaturization of sensors and high-performance optoelectronic devices [10,11] . According to earlier report, randomly arranged ITO nanorod arrays could be used as fluorescent labeling of biomolecules as well as surface-enhanced Raman signal detection [12][13][14][15] . Recently, we found that such ITO nanorod arrays can also be used as visible or UV detectors.…”
Section: Introductionmentioning
confidence: 99%